Job Motivation and Its Impact on Supporting Security Creativity and Innovation: An Applied Study on the General Command of Sharjah Police - Abdullah, Amna Ali Hassan (Journal of Economic, Administrative and Legal Sciences, 2024)
The current study aimed to identify job motivation and its impact on supporting creativity and security innovation, as well as identifying the foundations for developing creative and innovative skills among individuals and police officers and identifying the relationship between job motivation and creative and innovative skills. The study relied on the applied descriptive approach as the approach the appropriate method that achieves the objectives of the study, and was applied to a sample of 285 members of the Sharjah Police General Command.The problem of the study was represented in the need for employees of police institutions to have special skills in order to help them fulfill the tasks and burdens of security work efficiently, and this requires finding security leaders who have the ability to lead change with the skill of motivation to support police creativity and innovation.Among the findings of the study is that the concept of job motivation refers to those factors that contribute to raising the functional efficiency of workers in the Sharjah Police General Headquarters, and the process of providing incentives in the security field depends on a set of practical considerations and means such as relying on the plans of the Ministry of Interior, which are Through adopting the timetable and eligibility criteria for job incentives, scientific studies are concerned with the field of job incentives, due to their ability to raise the level of security, personal, intellectual, and technical skills in the security field.
Keywords: Job motivation; creativity; security innovation; police